163k views
5 votes
Solve. -2x-1-2x+43=97+7x

1 Answer

2 votes
Hey there! :)

-2x - 1 - 2x + 43 = 97 + 7x

Add like terms!!

(-2x - 2x) + (-1 + 43) = 97 + 7x

Simplify.

-4x + 42 = 97 + 7x

Now, we have to isolate x. To do this, we must subtract 42 from both sides.

-4x = 97 + 7x - 42

Then, subtract 7x from both sides.

-4x - 7x = 97 - 42

Simplify.

-11x = 55

Divide both sides by -11.

x = -5

~Hope I helped!~
User Silenus
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.